Efficacies and Impediments in Large Cardamom Farming in Ilam, Nepal - Bhattari, Thakur (Economic Journal of Development Issues, 2018)
Among all agricultural products produced in Nepal, large cardamom is the most expensive commercial crop with the highest export potential. The crop was initiated in Ilam. And, Ilam remained in the top four among large cardamom producing districts in Nepal up to 2014/15. Hence, the district deserves a pedagogic and appreciable place in its cultivation. The district was purposively selected for the analysis of its efficacy and blemishes. For this, primary data were collected during 2007 and 2014.The main efficacies of the crop were its high price, use of marginal land in cultivation, use of manpower mostly during off-season of other farming, need of less capital, and a common (familiar) crop. Suitable climate, rainfall, temperature range, export performance, tariff advantages, and availability of varieties were other plus points of the crop. The promises in its cultivation included prospects of quality improvement, growth in productivity, and easy approach to market. The challenges and weaknesses of the crop included diseases, lack of disease free saplings and seedlings, price fluctuations, drying of water sources for irrigation, and lack of government support in its cultivation and marketing. The crop was found popular in the study area due to its efficacies, which had outstripped its blemishes or flaws. Economic Journal of Development Issues Vol. 21 & 22 No. 1-2 (2016) Combined Issue, Page: 42-54